UNCOVER LOCAL WISDOM VALUE OF TRADE AT THE BORDER OF INDONESIA-MALAYSIA: AN ISLAMIC ECONOMICS PERSPECTIVE - Budi Iswanto; Munadi Munadi; Suriadi Suriadi (Share: Jurnal Ekonomi dan Keuangan Islam, 2020)
This article focuses on the study of local wisdom values of trade at the Indonesia-Malaysia border (in Perspective of Islamic Economics and Islamic teachings). The research location is in the community of Temajuk Sub-district which is directly adjacent to Malaysia. The trading activities undertaken by the Temajuk community have a local value that shows the relation with Islamic values, as well as the value of Islamic teachings. Local wisdom values of Temajuk Malay culture like Belalle ', Talangge ', Sikutuan, and Taware ' in a trading perspective are found in the indigenous ethnolinguistic Malay Temajuk. Ethnolinguistics is the value applied in Temajuk Malay customary as a form of communication which also has the value of Sharia trading. Ethnolinguistics above contains the value of Falah in trade, the form of Ethnolinguistics in trade communications is known by the Malay Community Temajuk and already being applied in the acceptance of trade, but the understanding of the values Contained in the indigenous Ethno linguistics  Malay Temajuk has not been known by the Temajuk Malay community, it is due to the interruption of the transfer of values between generations. So that the process of internalization of value needs to be conducted so that cultural functions as a manifestation of ideas that form the behavior of communities in trade can be implemented.========================================================================================================Menguak Nilai-nilai Kearifan Lokal dalam Perdagangan di Perbatasan Indonesia-Malaysia: Suatu Perspektif Ekonomi Islam. Artikel ini memfokuskan pada kajian Nilai-Nilai Kearifan Lokal Perdagangan Daerah Perbatasan Indonesia-Malaysia (Dalam perspektif Ekonomi dan Pendidikan Islam). Dengan mengambil lokasi penelitian pada masyarakat di Daerah Temajuk yang berbatasan langsung dengan Malaysia. Kegiatan perdagangan yang dilakukan masyarakat temajuk ternyata memiliki nilai lokal yang menunjukan keterkaitan nilai ajaran Islami, serta nilai pendidikan Islam. Nilai-nilai kearifan lokal budaya Melayu Temajuk seperti belalle’, talangge’, sikutuan, dan taware’ dalam perspektif perdagangan terdapat dalam etnolinguistik adat Melayu Temajuk. Etnolinguistik tersebut merupakan nilai yang diaplikasikan dalam adat Melayu Temajuk sebagai bentuk komunikasi. Dan memiliki nilai perdagangan syariah. Etnolinguistik di atas mengandung nilai falah dalam perdagangan, bentuk etnolinguistik dalam komunikasi perdagangan diketahui oleh masyarakat Melayu Temajuk dan telah diaplikasikan dalam transaksi perdagangan, namun pemahaman terhadap nilai-nilai yang terkandung dalam etnolinguistic adat Melayu Temajuk tersebut belum diketahui oleh masayarakat Melayu Temajuk disebabkan terputusnya transfer nilai antar generasi. Sehingga proses internalisasi nilai perlu dilakukan, agar fungsi budaya sebagai wujud ide dan gagasan yang membentuk prilaku masyarakat dalam perdagangan yang dapat diimplementasikan.